ANALYSIS OF FACTORS AFFECTING AUDIT QUALITY: INDEPENDENCE, WORKLOAD, AUDIT FEE, AND AUDITOR EXPERIENCE AT PUBLIC ACCOUNTING FIRMS IN BALI - Ni Nyoman Tria Nadyanti; I Dewa Nyoman Badera (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
An analysis of the factors influencing audit quality is crucial to ensuring the integrity and reliability of financial statements. Audit quality is affected by several variables, including independence, workload, audit fee, and auditor experience. This study adopts a quantitative approach with an associative design, collecting data through questionnaires administered to 50 external auditors working at Public Accounting Firms (KAP) in Bali Province. Data were processed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method via SmartPLS version 4.0 software. The findings reveal that independence, workload, audit fee, and auditor experience have a positive and significant effect on audit quality. These results support the theoretical framework of attitude behavior theory and attribution theory, which explain how both internal and external factors of auditors influence the audit process and outcomes. The theoretical and practical contributions of this study are expected to serve as a basis for developing professional standards and improving audit quality in Public Accounting Firms, particularly in Bali.